Inter‐arm difference in blood pressure in patients referred to tertiary hypertension center: Prevalence, risk factors, and relevance to physicians. Issue 8 (9th August 2020) - Jegatheswaran, Januvi; Hiremath, Swapnil; Edwards, Cedric; Ruzicka, Marcel
Abstract: The prevalence of inter‐arm BP difference is high in hypertension and is associated with adverse cardiovascular outcomes. We performed a retrospective chart review of prevalent patients in the Ottawa Hospital Hypertension Center to assess for prevalence, risk factors, and whether finding of inter‐arm BP difference >10 mmHg leads to investigations of the aorta and aortic arch. Inter‐arm BP difference among 493 patients was present in 16.2% (95% confidence interval [CI]13.3‐19.9%), and it was associated with presence of peripheral arterial disease. Physicians did not investigate ascending aorta and aortic arch for causes of the clinically significant inter‐arm BP difference.